Relatório do XVIII Colóquio de Estudantes de Geografia UNMSM, Peru 2022 - Aycate Chipana, Paula Marcela (2021)
Geography is one of the sciences that is most influenced by circumstances outside of knowledge itself, therefore in Peru, for many decades, the dissemination of geographic knowledge has been highly recognized in various fields and has been an important contribution to the history of Peru in all aspects, recognized geographers and geographers of our country such as Javier Pulgar Vidal, Carlos Peñaherrera, Bertha Balbin and among other characters of the Peruvian geography that will continue to be latent in the investigation. In the Universidad Nacional Mayor de San Marcos, students from the professional school of geography annually organize colloquiums on the dissemination of research work on different topics and although this event in particular was organized in the post-pandemic context, it did not prevent it from being held. The event entitled XVIII Colloquium of Geography Students UNMSM was carried out by the students of base 18 of the school of geography under the motto “Geographic Resilience in times of pandemic”.